The Role of Universities in Empowering Individuals and Society in Afghanistan - Fayaz Gul Mazloum Yar; Hameedullah Muzammil (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
Universities are not independent entities separate from society; they are influenced by political and social systems and possess significant abilities to influence various sectors. As a decision-making system, universities play a crucial role in creating suitable conditions for nurturing transformative leaders. The institutional foundation of universities aims to address the developmental needs of society. A successful university believes in itself and seeks indigenous solutions to real problems. The primary objective of this research is to examine the role of universities as the highest educational and training institutions in empowering individuals and society. Initially, the study explored the literal and terminological meanings of empowerment. Then, we highlight the most important functions of universities concerning individual and societal empowerment. After clarifying universities’ role as the highest educational and training institutions, we addressed the question of how universities can effectively contribute to the empowerment of individuals and society. This research adopts an analytical approach that examines and analyzes expert opinions, literature reviews, and previous studies.